Ekopopulisme pada Pengelolaan Hutan Adat di Desa Haruyan Dayak Kabupaten Hulu Sungai Tengah - Fatahilah, Muhammad Ibnu; Hamid, Ismar (Huma: Jurnal Sosiologi, 2025)
Forests play a vital role in sustaining the lives of Indigenous communities, as seen in Haruyan Dayak Village, South Kalimantan. This study aims to examine the contestation of knowledge in the management of customary forests in the village. Using a qualitative method with a phenomenological approach, data were collected through observation, semi-structured interviews, and documentation, and analyzed using the Manual Data Analysis Procedure (MDAP). The findings reveal that the people of Haruyan Dayak Village have a profound and enduring relationship with customary forests, which have long been an integral part of their lives. Their intensive interaction with nature has fostered deep spiritual and cultural attachments, reflected in traditions, cultural practices, and local beliefs that uphold forest preservation. The management of forests by the Indigenous community reflects an eco-populist paradigm, where forests are utilized as a source of livelihood while ensuring sustainability through local values and practices. This demonstrates that Indigenous communities not only depend on forests economically but are also deeply committed to their preservation. Thus, forest management rooted in local wisdom and Indigenous beliefs can serve as a sustainable model for natural resource conservation. This study contributes academically to the development of environmental sociology and political ecology, while also providing practical insights for strengthening the role of Indigenous communities in the sustainable management of customary forests and addressing related challenges. Further research is recommended to explore the sustainability of local values and Indigenous beliefs in forest management, particularly under the pressures of social, cultural, and policy changes.